PENERAPAN PRINSIP COMMUNITY BASED TOURISM DALAM PENGEMBANGAN WISATA DAN HOMESTAY DI DESA WISATA HIJAU SESAOT-LOMBOK BARAT - Anak Agung Ngurah Sedana Putra; Lalu Ahmad Zaki; I Wayan Adi Putra Ariawan (Jurusan Pariwisata Politeknik Negeri Kupang, 2023)
The green tourist village area is a tourist destination which is currently becoming a trend. Green tourist villages offer psychological healing for tourists with natural charm that is natural and free of pollution. In NTB itself there are several green tourism villages that have developed homestays within CBT, one of which is Sesaot Village, Narmada District, West Lombok district, NTB. The research method used is this research uses qualitative research methods. Researchers try to describe the actual conditions or circumstances by collecting data and information in the field and explaining in the form of descriptions without testing hypotheses or making previous predictions. Based on the research conducted, in fact seen from several aspects, communication related to business development planning based on CBT principles is considered not to have been carried out properly, both village- owned enterprises and local community do not understand each other's duties so that every decision in the development effort is taken unilaterally.